2018
DOI: 10.1021/acs.jchemed.8b00220
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond Alpha: A Primer on Alternative Sources of Single-Administration Reliability Evidence for Quantitative Chemistry Education Research

Abstract: This methodological paper examines current conceptions of reliability in chemistry education research (CER) and provides recommendations for moving beyond the current reliance on reporting coefficient alpha (α) as reliability evidence without regard to its appropriateness for the research context. To help foster a better understanding of reliability and the assumptions that underlie reliability coefficients, reliability is first described from a conceptual framework, drawing on examples from measurement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 69 publications
1
80
0
1
Order By: Relevance
“…To determine the appropriate statistic to use as an estimate of the internal consistency of our instrument scales, we ran single-factor CFAs for each of the three factors using both a congeneric model (i.e., unrestricted factor loadings) and a tau-equivalent model (i.e., all factor loadings are forced to be equivalent; Komperda et al. , 2018b ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the appropriate statistic to use as an estimate of the internal consistency of our instrument scales, we ran single-factor CFAs for each of the three factors using both a congeneric model (i.e., unrestricted factor loadings) and a tau-equivalent model (i.e., all factor loadings are forced to be equivalent; Komperda et al. , 2018b ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the sample size met the minimum criteria of five participants per item. Since we did not expect certain items within a construct to be more important than others in describing the construct, we followed the guidelines provided by Komperda et al (2018) and used the Tauequivalent indicator. In this process, all factor loadings within the same factor are set to be identical to ensure that each item within the same construct is equally weighted.…”
Section: Internal Structurementioning
confidence: 99%
“…Testing for internal consistency provides evidence that respondents to an instrument answer similar items in similar ways. The internal consistency of the survey was measured with Cronbach's alpha coefficient since it has been suggested to be an acceptable reliability measure for Tau Equivalent models (Komperda et al, 2018). A cut-off value of > 0.7 is recommended (Komperda et al, 2018;Streiner, 2003).…”
Section: Internal Consistencymentioning
confidence: 99%
“…In the congeneric model, the degrees of association between each item and the common construct are not necessarily the same, while in the tau-equivalent model, the factor loadings are restricted to be equivalent (Cho and Kim 2015;Graham 2006;Harshman and Stains 2017). Cronbach's Alpha is appropriate under a condition when the assumptions for the tau-equivalent model are met, and Omega is suitable when the assumptions for the tau-equivalent model are not met but fit for the congeneric model (Komperda, Pentecost, et al 2018). In this study, as shown below, two items fit the tau-equivalent model and three items fit the congeneric model.…”
Section: Data Analysis Strategymentioning
confidence: 93%
“…Consequently, an overall internal consistency value or a single-administration reliability coefficient for each interaction scale was calculated (Komperda, Hosbein, and Barbera 2018). Secondly, to determine which coefficient was appropriate in this study, a single-factor CFA model for each interaction scale was analysed using the congeneric and tau-equivalent models (Komperda, Pentecost, and Barbera 2018). In the congeneric model, the degrees of association between each item and the common construct are not necessarily the same, while in the tau-equivalent model, the factor loadings are restricted to be equivalent (Cho and Kim 2015;Graham 2006;Harshman and Stains 2017).…”
Section: Data Analysis Strategymentioning
confidence: 99%